Controlled release, organic or organomineral fertilizers for areca palm production - Ferraz, Marcelo Vieira [UNESP]; de Godoy, Leandro José Grava [UNESP]; Stucchi, Giovana [UNESP]; Reis, Antonio Gabriel Pontes Dos [UNESP]; Pacheco, Marco Aurelio Amado [UNESP] (FapUNIFESP (SciELO), 2022)
The areca palm is an ornamental plant widely used in Brazil for decoration and landscaping. The proper use of fertilizers and balanced fertilization are among the main factors that promote the rapid development of these plants and affect their technical and economic aspects. Because of the need to elucidate areca palm nutrition, this study aimed to evaluate the use of mineral (conventional or controlled release), organic, or organomineral fertilizers in the production of areca palm in pots. The experiment was conducted for a year under a 70% shading screen using a completely randomized design, with seven treatments and six replications. The treatments consisted of different fertilizers: control: no fertilizer; mineral: 10-10-10; controlled release mineral: 14-14-14, mineral with 50% N and K release controls: 16-06-18, mineral: 13-05-13, organomineral: 16-06-09, and organic. The experiment consisted of measuring the vertical height of the plant and determining the Falker Chlorophyll Index (FCI) a and b. All fertilizers used in the experiment provided gains in growth and green color (Chlorophyll Index) in the areca palm grown in pots relative to the absence of fertilization. The three-month controlled-release fertilizer treatment produced the best results, positively impacting the areca palm production, both in terms of plant height and color, which are attributes that increase the product's commercial value.
Keywords: adubação; Dypsis lutescens H.Wendl; fertilization; nutrição de plantas; ornamental plant; plant nutrition; planta ornamental